Investigating the kinetics of small alcohol oxidation reactions using platinum supported on a doped niobium suboxide support - Keenan Black‐Araujo; Katherine Nguyen; Reza Alipour Moghadam Esfahani; E. Bradley Easton (Electrochemical Science Advances)
Abstract Platinum nanoparticles deposited on a silicon‐doped niobium suboxide support provided the catalyst known as Pt/NbOS. This was compared to the commercial Pt/C electrocatalyst in the ethanol and methanol oxidation reactions for use in direct alcohol fuel cells. Cyclic voltammetry and electrochemical impedance spectroscopy demonstrate that the employment of the metal oxide support provides higher peak oxidation currents and smaller charge transfer resistances during alcohol oxidation. Carbon monoxide (CO) stripping experiments showed enhanced removal of CO by Pt/NbOS compared to Pt/C. Pt/NbOS shows its smallest apparent activation energies of 13.3 and 11.9 J mol‐1, for methanol and ethanol oxidation respectively, which are 38% and 27% lower than those of Pt/C at the same potentials. This increased activity of Pt/NbOS is attributed to the strong metal‐support interactions between the active Pt nanoparticles and the NbOS support which demonstrate its utility in replacing Pt/C in methanol and ethanol fuel cells.